PENGARUH FAKTOR LINGKUNGAN IBU DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH PESISIR - Susilawati Susilawati; Meilisa Luthfiah (CV. ADIBA AISHA AMIRA, 2023)
Background: Environmental factors and maternal personal hygiene are related to the incidence of diarrhea. One of them is the presence of vectors caused by poor sanitation and SPAL and CTPS. Purpose: This literature review aims to determine the relationship between environmental factors and maternal personal hygiene with the incidence of diarrhea. Method: The method used in writing a literature review is a traditional literature review. Data sources come from Google Scholar and the Garuda portal in the 2015-2020 period. The keywords used are